Antimicrobial susceptibility, phylotypes, and virulence genes of Escherichia coli from clinical bovine mastitis in five provinces of China. Issue 1 (1st January 2020) - Lan, Tu; Liu, Huimin; Meng, Lu; Xing, Mengru; Dong, Lei; Gu, Mei; Wang, Jiaqi; Zheng, Nan
ABSTRACT: The objectives of this study were to determine the antimicrobial susceptibility, phylotype, and virulence genes of Escherichia coli ( E. coli ) from cows with clinical mastitis. A total of 497 mastitis samples were collected and 92 E. coli isolates were identified. E. coli isolates were highly resistance to ampicillin (41.3%), followed by piperacillin (36.9%) and tetracycline (34.7%). Five intimin types, namely μR-ι2, λ, ξR/β2, νR-ε2, η, were observed among 75 EPEC strains with eae gene, with all the intimins were first detected in bovine mastitis milk. And 65 E. coli strains (70.7%) belonged to seven different O serotypes (O121, O91, O22, O26, O128, O111, and O113). For the phylogroup assignment, only 87 E. coli isolates could be assigned into phylogroup B1, A, C, and E. This study suggested the prevailing among EPEC strains isolated from mastitis in five provinces was important to understand the etiology of E. coli .